2016
DOI: 10.1021/jacs.5b13449
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Controller of SNARE-Driven Membrane Fusion That Primes Vesicles for Ca2+-Triggered Millisecond Exocytosis

Abstract: Membrane fusion is mediated by the SNARE complex which is formed through a zippering process. Here, we developed a chemical controller for the progress of membrane fusion. A hemifusion state was arrested by a polyphenol myricetin which binds to the SNARE complex. The arrest of membrane fusion was rescued by an enzyme laccase that removes myricetin from the SNARE complex. The rescued hemifusion state was metastable and long-lived with a decay constant of 39 min. This membrane fusion controller was applied to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…As a result, a large energy barrier separates the folded and the unfolded CTD states, leading to a large hysteresis of the CTD transitions in the FEC. Finally, the half‐zippered state is supported by many other experiments, especially imaging by electron microscopy . Combining with earlier evidence, these observations corroborate that a half‐zippered trans‐SNARE structure is required for the calcium‐triggered synaptic vesicle fusion.…”
Section: Introductionsupporting
confidence: 81%
“…As a result, a large energy barrier separates the folded and the unfolded CTD states, leading to a large hysteresis of the CTD transitions in the FEC. Finally, the half‐zippered state is supported by many other experiments, especially imaging by electron microscopy . Combining with earlier evidence, these observations corroborate that a half‐zippered trans‐SNARE structure is required for the calcium‐triggered synaptic vesicle fusion.…”
Section: Introductionsupporting
confidence: 81%
“…Single-molecule imaging was carried out on an objective-type total internal reflection fluorescence (TIRF) microscope built around Olympus IX73 (Supplementary Fig. 1a ) similar to previous work 3 . Combined via a polarizing beam splitter, a green laser (Cobolt 06-DPL,532 nm), for excitation of Cy3B) and a red laser (Cobolt 06-MLD, 638 nm) with a laser clean-up filter were coupled to a single mode fiber.…”
Section: Methodsmentioning
confidence: 99%
“…We used polyethylene glycol (PEG)-coated flow chambers as described elsewhere 1 , 3 except the experiments of Atto647N blinking dynamics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, biologists have discovered several details about the function of this protein complex, about its structure, and about the mechanism that enables the lipid bilayers fusion. Specifically, several experiments have shown that a partially assembled SNARE complex exists as an intermediate state during vesicle exocytosis (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The presence of such an intermediate state is critical for the kinetic of exocytosis.…”
Section: Introductionmentioning
confidence: 99%